"AMERICAN IDIOT" SONGS: ON SEMIOTIC PERSPECTIVES - Rizqi Husaini; Dwi Setyadi; Puput Jianggimahastu L.S. (LINGUAMEDIA Journal, 2020)
This research aims to find out the meaning contained in the song American Idiot, which was popularized by Green Day. Apart from that, about the link between the song and what is happening now. This article uses a qualitative approach, where data sources are obtained from articles, news, and interviews. From this research, it can be seen that this song contains criticism of the songwriter wants to convey about his country. This song is also very relevant in describing what is happening right now. Keywords: American Idiot, Green Day, Semiotic, Sign